Analisis Perencanaan SDM Kesehatan Berdasarakan Metode ABK Kes Unit Rekam Medis Rawat Jalan Di UPTD Puskesmas Jatiroto Wonogiri: Analisis Perencanaan Sdm Kesehatan Berdasarakan Metode ABK Kes Unit Rekam Medis Rawat Jalan Di UPTD Puskesmas Jatiroto Wonogiri - Arifatun Nisaa (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
At the Jatiroto Wonogiri Health Center there are 2 outpatient registration officers who have entered their retirement period so that human resource planning is needed so that medical record management activities are optimal. workload standards, supporting task standards and the need for the number of health human resources at the Jatiroto Health Center UPTD. The type of research used is descriptive qualitative. The subjects of this study were the head of medical records and the head of the puskesmas, while the object was the activities of the medical record personnel. Data was collected by observation and interviews with research subjects. The results of the calculation of ABK Kes show that the available working time is 1,200 hours/year or 72,000 minutes/year, the need for outpatient medical record workload for the main task is 432,000 minutes/year and for supporting tasks is 600 minutes/year and the calculation of HRK needs for medical records is 5 workers. in the outpatient medical record unit UPTD Jatiroto Health Center.